ANALISIS FAKTOR YANG MEMPENGARUHI KINERJA MANAJER PADA PERUSAHAAN MANUFAKTUR DI JAWA TENGAH - Tri Nur Wahyudi (Department of Accounting Education, Faculty of Teacher Training and Education Universitas, 2015)
The aims of this study is to analyse whether the following factors: accounting information, budgeting participatory, environment, working experience and level of education have impacts on managers’ performance and to investigate which factor has the most dominant impact on managers’ performance. The data in this study were questionnaires completed by 50 production managers working in 50 manufacture companies in Central Java. The data were analyzed using SPSS application version 15,0. The study found that based on simultaneous evaluation accounting information, budgeting participatory, environment, working experience and level of education have positive impacts on managers’ performance with influence adjusted intensity R2=0,909 or 90,9% whereas the other 9,1% were explained by other variables not included in the model. Based on partial evaluation accounting information, budgeting participatory, working experience and level of education factors had positive impacts on manager performance whereas environment factor did not have any impact on manager performance. Among the factors investigated, the accounting information had the most dominant impact on managers' performance.